Status problems and directions of the SPED program at the Silahis ng Kalusugan, Philippine General Hospital, Division of City Schools Manila - Samson, Estelita Mabanglo (Manila : National University, 2001)
This study derives its rationale and significance from the imperatives of providing continuous education. For the chronically-ill children, educational continuity is of vital concern. Absences from classes are often frequent and recurrent that adds up to a substantial amount of missed school time. Weak as they are physically, these children have the right to equal access to quality education, including other related laws which provide training and education to special learners.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.